1997
DOI: 10.1200/jco.1997.15.12.3464
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel, carboplatin, and extended-schedule etoposide in the treatment of small-cell lung cancer: comparison of sequential phase II trials using different dose-intensities.

Abstract: Paclitaxel can be added at full dose (200 mg/m2) to a carboplatin/etoposide combination while maintaining a tolerable toxicity profile. Median survival times in both extensive- and limited-stage patients compare favorably with other reported regimens. This regimen merits further investigation, and a randomized trial to compare this regimen with a standard carboplatin/etoposide combination is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 17 publications
1
25
2
Order By: Relevance
“…The number of fatal septic episodes was somewhat surprising, because the incidence of Grade 4 leukopenia with this three-drug regimen was not substantially higher than we previously reported with the paclitaxel, carboplatin, and etoposide regimen. 9 In contrast to the current regimen, we observed a treatment-related fatality rate of only 3% in a group of 79 patients with the paclitaxel, carboplatin, and etoposide regimen. In the current trial, most of the treatment-related deaths were observed in patients with a poor performance status (ECOG 2); 5 of 12 patients with a poor performance status who were enrolled in this trial had fatal toxicity.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The number of fatal septic episodes was somewhat surprising, because the incidence of Grade 4 leukopenia with this three-drug regimen was not substantially higher than we previously reported with the paclitaxel, carboplatin, and etoposide regimen. 9 In contrast to the current regimen, we observed a treatment-related fatality rate of only 3% in a group of 79 patients with the paclitaxel, carboplatin, and etoposide regimen. In the current trial, most of the treatment-related deaths were observed in patients with a poor performance status (ECOG 2); 5 of 12 patients with a poor performance status who were enrolled in this trial had fatal toxicity.…”
Section: Discussioncontrasting
confidence: 68%
“…This regimen had a high level of activity, with a median survival in patients with extensive stage disease and limited stage disease of 10 months and 25 months, respectively. 9 Early experience with a regimen containing paclitaxel and topotecan also yielded impressive results, including a median survival of 12 months in a small group of patients with extensive stage disease. 10 In a further attempt to incorporate topotecan into first-line combination therapy for patients with small cell lung carcinoma, we performed a Phase I trial to determine the optimum doses of paclitaxel, carboplatin, and topotecan when used in combination.…”
mentioning
confidence: 99%
“…Like paclitaxel, carboplatin has radiosensitising properties, which makes the combination of the two drugs with radiotherapy interesting . Hainsworth et al (1997) have investigated the combination of carboplatin, paclitaxel and etoposide in a dose escalation study in 1997. Concurrent TRT was given during cycle 3 and 4 to patients with LS (45 Gy in 25 fractions) and was considered acceptable.…”
mentioning
confidence: 99%
“…In two phase II studies it produced an ORR of 34% and 41% in unpretreated patients with extensive disease (Kirshling et al, 1994;Ettinger et al, 1995). It has also been tested in combination with cisplatin (or carboplatin) and etoposide with promising preliminary results (Levitan et al, 1995;Kelly et al, 1996;Hainsworth et al, 1997;Glisson et al, 1999).…”
mentioning
confidence: 99%